Comment lutter contre les effets négatifs de la fatigue mentale : une revue narrative - Jacquet, T.; Poulin-Charronnat, B.; Lepers, R. (Movement & Sport Sciences - Science & Motricité, 2023)
Mental fatigue is a physiological phenomenon that induces an impairment of cognitive and physical performances. Many studies have been conducted in recent years to determine how to prevent and/or limit and/or compensate for the deleterious effects of mental fatigue. The objective of this narrative review of the literature is to propose a synthesis of all the work carried out. A large disparity in the methods used should be noted, whether concerning the strategies used (bioactive versus non-bioactive) or the timing of intervention (before, during or after the performance of a mentally fatiguing task). Caffeine, the most studied substance, seems to be particularly effective in overcoming mental fatigue with beneficial effects on subjective, physiological or behavioral markers. Other strategies, such as using creatine, listening to music, or physical activity, also seem promising. The beneficial effects of the different methods have been attributed to their positive impact on motivation and/or their stimulating effect on the dopaminergic system. However, future studies are still necessary to further evidence the mechanisms underlying the beneficial effects of the different strategies proposed.